Promoting social emotional competence [videorecording] - Center on Social and Emotional Foundations for Early Learning (Champaign, IL Center on Social and Emotional Foundations for Early Learning, 2005)
"This series of videoclips serve as a foundation for several activities that have been developed to support early childhood professionals in developing their skills in the area of promoting young children's social and emotional development and preventing challenging behaviors"
Keywords: Child development; Social skills in children; Emotions in children; Preschool children